2015
DOI: 10.1111/jth.12773
|View full text |Cite
|
Sign up to set email alerts
|

Central venous catheter‐related thrombosis and thromboprophylaxis in children: a systematic review and meta‐analysis: reply

Abstract: children to thromboprophylaxis is justifiable against the natural history of CVC-related DVT. We argue that natural history studies that prospectively follow patients with a CVC in situ with concurrent objective imaging and long-term evaluation of clinical outcomes, such as PTS, are the logical next step in developing appropriate clinical management. AddendumAll authors read the paper by Vidal et al. This Letter to the Editor was drafted by S. Jones and F. Newall, with review and editing by V. Ignjatovic and P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Although children, in general, have lower risks for VTE, it seems to be least common with umbilical venous catheters and PICC lines. The risk appears similar in both upper and lower extremities 46 . Again, the risks and benefits of CVC placement must be considered prior to placement in children.…”
Section: Complications—venous Thromboembolismmentioning
confidence: 99%
“…Although children, in general, have lower risks for VTE, it seems to be least common with umbilical venous catheters and PICC lines. The risk appears similar in both upper and lower extremities 46 . Again, the risks and benefits of CVC placement must be considered prior to placement in children.…”
Section: Complications—venous Thromboembolismmentioning
confidence: 99%
“…Studies are contradictory as to which type of CVC, insertion technique, or catheter material has the highest risk for DVT development. A meta‐analysis found that DVT rates were lowest in patients who had PICCs and umbilical lines (versus tunneled lines), without a difference in DVT rates between CVCs placed in the upper or lower extremity . Conversely, a systematic review found tunneled lines (versus nontunneled and PICCs) to have the lowest rate of DVT …”
Section: Risk Factorsmentioning
confidence: 99%
“…Securing reliable venous access is of paramount importance when considering parenteral nutrition (PN). However, the presence of a central venous catheter (CVC) is the principal risk factor for major, potentially lethal complications, such as nosocomial bloodstream infection [1] and venous thrombosis [2]. Moreover, the most important risks associated with complications arising from the use of CVC are administration of PN, young age and extended use (long indwelling time) [3e5].…”
Section: Introductionmentioning
confidence: 99%